Feasibility and Acceptability of a Cognitive Behavioral Therapy-Based Smartphone App for Smoking Cessation in China: A Single-Group Cohort Study - Liao, Yanhui; Tang, Jinsong (Frontiers in Psychiatry, 2022)
Background: Previous research has suggested that mobile phone applications (apps) may potentially increase quit rates. The purpose of this single-group cohort study sought to examine the feasibility and acceptability of a novel smartphone-based smoking cessation app designed for smoking cessation in China. smoking quit rate. Methods: A total of 180 smokers from two cities of mainland China with willingness to make a quit attempt were invited to this smoking cessation app program, a cognitive behavioral theory (CBT)-based smoking cessation intervention via a smartphone app. Participants received 37-44 days intervention (including 7-14 days’ pre-quit preparation and 33 days’ intervention from quit date). Feasibility and acceptability of the program, and smoking status were assessed at baseline stage (initial installation), pre-quit stage and post-quit stage (day 7, day 15, day 33 after quit date). Results: A total of 163 (90.6%) participants completed the study. Among then, 76%  89% of participants logged into the app ≥ 1 time per day across stages (at baseline, during pre-quit stage and day 7, 15 and 33 of post-quit stage); approximately 90% of participants were satisfied with the app across stages. A significant rise of self-reported overall satisfaction with the app is observed from baseline (93% at Time 1) to the end of the program (98% at Time 2, 33 days after quit date) (p=0.021). Participants who believed/agreed this app can help them to quit smoking significantly increased from 69% at baseline to 97% at day 33 after quit date (p0.001). Participants were satisfied with most (80%  90%) of the features, especially the information feature. Intention-to-treat analysis showed that the percentage of 33-day self-reported continuous prevalence abstinence was 63.9%, and seven-day point prevalence abstinence rate was 81.7%, 87.2% and 77.8% at day 7, 15 and 33 after quit date respectively. Conclusions: This study demonstrated the feasibility and acceptability of the smartphone app intervention for smoking cessation and introduced a new digital treatment model which is expected to overcome barriers facing in accessing traditional in-person smoking cessation services and extend nationwide smoking cessation services in China.